Effect of Allelopathic potential of aqeous extracts from Paspalum distichum L. and Cyperus spp. L. leaves on germination and growth of some accompanying weeds of Rice Oryza sativa L. - كاظم عبد الرضا, كوثر; ياسر حافظ العيساوي, علي; غسان حسين, حوراء (University of Thi-Qar Journal of Science, 2017)
This experment was carried out in the Season (2014 - 2015) to assess The inhibtory activity of plants Paspalumdistichum L., and Cyperus spp. L.. Water and alkhol extracts on germination and growth of Cyperus odoratus L.,Diplanche fusca Beaur (L.). and Echinocholoa crus-galli L. Seeds of the test plants Culturing in petridishes then treated with water and alkehol extracts at concentrations of (0%, 40%, 60% 80% and 100%) .Plant extracts showed asignificant reduction of germination percentage, velocity coefficient of germination, shoots and roots length and their dry weight, of all test species; principally on the increased concentration till 100%; except the low concentrations were markediy Stimulated in shoots length, shoots and roots dry weight in Cyperusodoratus L. coefficient velocity of germination, shoots length in Medicago hispida L., shoots length in Sonchus oleraceus L.